Contamination of atmosphere with volatile hydrocarbons during handling oil products of petrol and diesel fuel types - Chýlková, Jaromíra; Šelešovská, Renáta; Stuchlík, Martin; Machalíková, Jaroslava (Univerzita Pardubice, 2010)
The paper describes monitoring of contamination of atmosphere with organic substances during ordinary operation of a petrol station, namely during pumping of fuel by a consumer. The measurements were performed by means of a portable analyser ECOPROBE 5 equipped with an IR detector. The analyser was calibrated using standard mixtures of petrol vapours and air as well as by means of gaseous standards of volatile portions of Diesel fuel. The calibration curves obtained were used for determination of real concentrations of the analysed substances in the units of mg m–3. The practical measurements have shown that the reverse exhaust of petrol vapours cannot prevent contamination of the atmosphere unless the dispensing nozzle is properly inserted during filling the tank.
Keywords: contamination; petrol station; petrol vapours